PEDAGOGICAL WAYS OF COGNITIVE COMPETENCES IN FUTURE TEACHERS BASED ON ACMEOLOGICAL APPROACH (World Economics and Finance Bulletin, 2024)
This article analyzes cognitive competence skills based on the acmeological approach. Based on this approach, the pedagogue gets a high result in developing his professional skills. At the same time, if the aspects of professional adaptation of future teachers are studied, pedagogical conditions are determined, if the project of professional adaptation of future teachers is put into practice based on a systematic approach, the desired goal will be achieved